Faktor yang Mempengaruhi Manajemen Laba Pada Perusahaan di Indonesia - Mhd Purwo Pranyoto; Debbi Chyntia Ovami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to examine the effect of capital structure, liquidity, profitability and firm size on earnings management in food and beverage companies listed on the Indonesia Stock Exchange in 2018-2020. Determining the sample using the purposive sampling method, samples obtained by 11 food and beverage companies from 2018-2020 in order to obtain 33 observational data. This research data is secondary data with multiple linear regression analysis technique (multiple linear regression method) to test the assumptions for the feasibility of the data. The data processing used in this study uses panel data regression with the help of Eviews 10 software. The results of this study found that capital structure has a negative and significant effect on earnings management, liquidity has a positive and insignificant effect on earnings management, company size has a negative and insignificant effect. to earnings management earnings management. However, profitability has no significant effect on earnings management. Meanwhile, based on the results of the simultaneous test (F test) that all independent variables simultaneously and significantly affect the dependent variable.